2018
DOI: 10.1002/pen.24792
|View full text |Cite
|
Sign up to set email alerts
|

Deformation behavior of thermoplastic elastomer specimens: Observation of the strain behavior in a wide range of tensile speeds

Abstract: During the tensile testing of thermoplastic elastomers it is difficult to obtain true stress–strain curves because of necking phenomenon. Thus, we conducted a high‐speed tensile testing of Thermoplastic polyester elastomer's (TPC) notched specimens with strain measurement using digital correlation and reported the true stress–strain relations under various tensile speeds in this study. Because notched specimens enable control necking position, TPCs vary depending on the composition and composition ratio of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
(63 reference statements)
1
2
0
Order By: Relevance
“…2A). This was consistent with an increase in the yield strength and the elastic modulus in thermoplastic materials with increasing deformation rate (29,30). For a given fiber, the spring diameter and the spring index of the actuators formed by cold drawing were controlled by the deformation rate and the maximum applied strain (Fig.…”
supporting
confidence: 80%
“…2A). This was consistent with an increase in the yield strength and the elastic modulus in thermoplastic materials with increasing deformation rate (29,30). For a given fiber, the spring diameter and the spring index of the actuators formed by cold drawing were controlled by the deformation rate and the maximum applied strain (Fig.…”
supporting
confidence: 80%
“…Strength and stiffness of polymers' materials depend on the strain rate. Abdo et al [30,31] and Isogai et al [32] incorporated thermoplastic polyester elastomers (TTPE) into short, glass fiber-reinforced PBT samples in order to investigate the strain speed dependence. The results indicated that ultimate tensile strength is sensitive to strain rate.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the total stress of TPEs can be divided into elastic and viscous parts, and the strain rate effect is mainly reflected in affecting the viscous stress contribution. The Eyring model, proposed by Eyring and modified by many other researchers, has been utilized to describe the viscous stress adequately, which depends on strain rate whether in semicrystalline polymers, amorphous polymers, or TPEs . In particular, the relationship between yield stress and strain rate has been given accurately by this model .…”
Section: Introductionmentioning
confidence: 99%